Was the Left’s Thunder Stolen? Soviet Short Films on British Wartime Screens - Jeremy Hicks (Connexe, 2019)
Following the Nazi invasion of the Soviet Union in June 1941, the United Kingdom witnessed a dramatic surge in support of and interest in its new Soviet ally against the Nazis. The British government began to help the Soviets, but was widely perceived to be doing too little. The Ministry of Information attempted to counter this impression, showing the government’s support for Russia, while at the same time trying to ensure that this support remained under governmental control and did not fall into the hands of British Communists. While scholarship has devoted a great deal of attention to the diplomatic dimension of Anglo-Soviet wartime relations, there has been little written about issues of culture and propaganda, which played a crucial role; likewise studies of cinema in wartime Britain have paid scant attention to the British wartime reception of Soviet film. During the first years of the Anglo-Soviet alliance, however, short films in particular proved an especially important medium for the communication of the British government’s complex policy on Soviet Russia: it was attractive with audiences for its combination of immediacy with authenticity, but also attractive to governments as a reliable transmission belt for a carefully calibrated message. As such, analysis of shorts with specific analysis of the key films: Salute to the Soviet, 100 Million Women enables us to reassess the claim that the Ministry of Information really succeeded in stealing the thunder of the Left, and reconsider the effects this policy had on British society.